Numerical and Analytical Study of Fluid Flow and Thermal Transfer in a Rough Fracture. (31st May 2022) - Wen, Xiangyue; Long, Xiting; Yang, Zhaoying
Abstract : The surface morphology of rough fractures significantly affects the fluid flow and heat transfer characteristics in the fractures. A thermal-flow coupling model with specific geometric fractures was established to investigate the influence of surface morphology on the heat transfer characteristics of a single fracture. The effect of temperature on the physical properties of rocks and fluids was included in the study to reflect the actual situation more realistically. The research results show that the temperature of the fluid in the rough fracture is nonlinearly distributed along the flow direction and the higher the flow velocity, the higher the heat transfer efficiency. The fracture surface morphology has a significant impact on the heat transfer characteristics, and the surface fluctuation will greatly affect the flow velocity, causing the fluid temperature to change abruptly at the fracture surface. Under the same flow rate, with the increase of the fluctuation degree of the fracture surface and the fluctuation frequency, the larger the heat exchange area of the fracture surface, the stronger the heat exchange performance. The heat transfer efficiency of the fracture is directly related to the heat transfer area of the fracture, so even with the same permeability, the heat transfer performance of fractures with different surface topography is different.